Application of CFRP Carbon Fiber in the bending reinforcement of reinforced concrete experimental beams in Huaraz city - Depaz Hidalgo, Fernando Javier (2021)
This article deals with the flexural reinforcement of reinforced concrete beams through carbon fiber reinforced polymer (CFRP), with the main objective of comparing the results obtained with a theoretical reinforcement design and those obtained in beams with CFRP reinforcement. tested under point load, as well as establishing the influence it has on the capacity of the beams to bending. The process of elaboration of the specimens with and without CFRP reinforcement and with the same amount of reinforcing steel is described, as well as the test carried out under point load to each beam, the amount of CFRP reinforcement is detailed, all this based on a beam obtained from the structural analysis carried out for a model building subjected to different overloads to generate an increase in the bending moment, making it necessary to place the CFRP reinforcement. Finally, the comparison between the results of the tests and those of the theoretical design is presented, showing that the CFRP reinforcement positively influences the bending capacity of the beams, although there is a difference in the theoretical-practical capacity, concluding that it should be considered a correction factor.